Relevant inputs analysis and its applications - Yan Wang; Gupta, Rajiv; Neamtiu, Iulian (Proceedings - International Symposium on Software Reliability Engineering, 2013)
In this paper we develop a dynamic analysis, named relevant input analysis, that characterizes the role and strength of inputs in the computation of different values during a program execution. The role indicates whether a computed value is derived from an input value or its computation is simply influenced by an input value. The strength indicates if role (derived or influenced) relied upon the precise value of the input or it is among one of many values that can play a similar role. While it is clear that the results of our analysis can be very useful for the programmer in understanding relationships between inputs and program behavior, we also demonstrate the usefulness of the analysis by developing an efficient delta debugging algorithm. Other applications of relevant input analysis include assisting in generating test inputs and detection of security holes.